Hypoglycemic and antioxidative activities of ethanol seed extract of Hunteria umbellate (Hallier F.) on streptozotocininduced diabetic rats - Ogunlana, Olubanke O.; Adetuyi, Babatunde O.; Rotimi, Miracle (Clinical Phytoscience, 2021)
Background: Diabetes, a global cause of mortality in developing countries is a chronic disorder affecting the metabolism of macromolecules and has been attributed to the defective production and action of insulin characterized by persistent hyperglycemic properties. This global disorder harms organs of the body such as the liver, kidney and spleen. Medicinal plants such as Hunteria umbellate have been shown to possess hypoglycemic, antioxidative and anti-diabetic properties owing to the high concentration of active phytochemical constituents like flavonoids and alkaloids. The present study seeks to evaluate the hypoglycemic activities of ethanolic seed extract of Hunteria umbellate on streptozotocin-induced diabetes rats. Methods: Thirty (30) female experimental rats were randomly divided into five groups with six rats per group and were administered streptozotocin (STZ) and Hunteria umbellate as follows. Group 1 served as control and was given only distilled water, group 2 rats were administered 60 mg/kg STZ; Group 3 was administered 60 mg/kg STZ and 100 mg/kg metformin; group 4 rats were administered 60 mg/kg STZ and 800 mg/kg Hunteria umbellate, group 5 rats 60 mg/kg STZ and 400 mg/kg Hunteria umbellate. The fasting blood glucose level of each rat was measured before sacrifice. Rats were then sacrificed 24 h after the last dose of treatment. Results: The results showed that Hunteria umbellate significantly reversed STZ-induced increase in fasting blood glucose and increase in body and organs weight of rats. Hunteria umbellate significantly reversed STZ-induced decrease in antioxidant enzyme in liver, kidney and spleen of rats. Hunteria umbellate significantly reversed STZinduced increase in oxidative stress markers in liver, kidney and spleen of rats
Keywords: Diabetes; Hunteria umbellate; Streptozotocin; lohor Esalomi; Alaba Adeyemi; Nigeria; Digital Development; Covenant University; ACE: Applied Informatics and Communication